ANALISIS KONTRIBUSI PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN DAERAH KABUPATEN SUMBAWA - Indah Lestari; S Syafruddin (Pusat Riset dan Publikasi, 2022)
This study aims to analyze the contribution of land and building tax (PBB) to the regional income (PAD) of Sumbawa Regency. This research is a descriptive study that aims to examine descriptively the contribution of PBB to the regional income of Sumbawa Regency in 2017-2021. The type of data used is quantitative data in the form of data on realization of land and building tax revenue, and or realization of total regional revenue for the Sumbawa Regency for 2017-2021 obtained from the Central Statistics Agency (BPS) for the Regency of Sumbawa in the form of documents and archives of the Financial Report of the Regional Government of the Sumbawa Regency for the year 2017-2021 which has been online published. The analysis technique used is percentage analysis as a comparison material between the target of PBB revenues and regional revenues with their realization so that the magnitude of the contribution of PBB to total Regional Revenue can be known. Based on the results of the research that has been conducted, it is known that the contribution of PBB to the regional income of Sumbawa Regency in 2017-2021 has fluctuated. The average contribution of PBB to the regional income of Sumbawa Regency for 2017-2021 is in the very low category. The level of contribution, which is always unstable every year, is due to the realization of PBB and the realization of PAD which are still fluctuating or fluctuating every year so that the criterion value for interpretation is always lacking.